2011
DOI: 10.1080/17430437.2011.546517
|View full text |Cite
|
Sign up to set email alerts
|

‘Over here’: ‘Americanization’ and the new politics of football club ownership – the case of Liverpool FC

Abstract: Americanisation and the New Economics of English FootballFrom around the late-1960s the discourse of cultural imperialism in academic theorising about popular culture tended to characterise the critical reception of globalisation by casting the associated processes as the diffusion of specifically American values, consumer goods and lifestyles [1]. Later, Roland Robertson"s influential work took a rather different route by seeking to establish globalisation as "the process whereby the world becomes a single pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…In the case of Coombs and Osborne (2012), the owner's targets and strategies were actively communicated with club stakeholders, which fostered a strong bond between the new ownership and the community. In contrast, Williams and Hopkins (2011) and Donnelly et al (2008) highlighted negative examples in their studies. Both the community of Liverpool FC and Celtic FC initially rejected commercialization plans, as cultural factors were not sufficiently acknowledged by the new owners.…”
Section: Investor Behavior and Strategymentioning
confidence: 92%
See 1 more Smart Citation
“…In the case of Coombs and Osborne (2012), the owner's targets and strategies were actively communicated with club stakeholders, which fostered a strong bond between the new ownership and the community. In contrast, Williams and Hopkins (2011) and Donnelly et al (2008) highlighted negative examples in their studies. Both the community of Liverpool FC and Celtic FC initially rejected commercialization plans, as cultural factors were not sufficiently acknowledged by the new owners.…”
Section: Investor Behavior and Strategymentioning
confidence: 92%
“…Bull and Whittam (2021) observed a detachment of local fans from foreign owned clubs, as the cultural capital of the clubs is exploited by the new ownership in a case study on English Premier League clubs. Williams and Hopkins (2011) investigated fan reactions at Liverpool FC in 2008 after the club was taken over by American businessmen. They found that fans were at odds with owners, paradoxically, because ownership tried to reproduce the cultural DNA of the club.…”
Section: Investor Perceptionmentioning
confidence: 99%
“…2 Similarly, as many Liverpool supporters protested between 2008 and 2010 against the apparent mistruths the 'club's' American (economic) owners, Tom Hicks and George Gillett, told, they repeatedly held aloft banners and handed out leaflets that declared it to be 'their' club (Millward, 2011(Millward, , 2012. Once again, the football club they 'owned' encompassed the myriad of cultural dimensions rather than, necessarily, its economic rights (Williams, 2012;Williams and Hopkins, 2011…”
Section: Hull City 'Tigers' and The Transnational Reach Of The Englismentioning
confidence: 99%
“…Equally, the emergence of supporter organizing as a social movement is worthy of attention although greater space is afforded elsewhere for this purpose (Millward, 2012; Williams, 2012; Williams and Hopkins, 2011) with a similar analysis made of the movement called Keeping Everton In Our City (KEIOC, see Fitzpatrick, 2013). 4 To specifically understand the historic working class embedded character of professional football within the city of Liverpool, of Everton FC and Liverpool FC, see Kennedy and Collins (2006) who make reference to the sectarianism and politics that seemed to couple together the two sets of supporters and clubs.…”
Section: Community Assets (And Football) In the Communitymentioning
confidence: 99%
“…By 2003, and coinciding with the start of the HMRI, the club had managed to pacify local residents and a formal planning application was submitted for a new stadium. At the same time, the then majority owner of the club pursued new investment amid concerns that the costs of a new stadium, believed to be necessary in terms of sporting competitiveness, would be prohibitive (Williams and Hopkins, 2011). This was confirmed by the North West Development Agency who were apprehensive about construction delays after previously committing a grant of £9 million to match European Objective I funds.…”
Section: The Supporters Union and The Listing Of Anfield Stadiummentioning
confidence: 99%